2015
DOI: 10.11138/ads/2015.6.2.035
|View full text |Cite
|
Sign up to set email alerts
|

A comparative, randomized, controlled study on clinical efficacy and dental staining reduction of a mouthwash containing Chlorhexidine 0.20% and Anti Discoloration System (ADS)

Abstract: SummaryIntroduction. A good control of bacterial plaque is an essential factor for the success of periodontal therapy, therefore it is the main objective that the clinician together with the patient must get to have a healthy periodontium. The plaque control with mouthwashes is the most important home therapy as it helps to reduce the formation of plaque between the mechanical removal with a toothbrush. Aim. Authors analyzed the clinical data from a trial carried out with 3 different mouthwashes containing 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This is important to keep in mind as it has been reported that the size and distribution of filler can be related to color changes [ 3 , 5 ]. In addition, some reports have related external discoloration of the resin composite to large filler particles as they provide increased surface roughness [ 17 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important to keep in mind as it has been reported that the size and distribution of filler can be related to color changes [ 3 , 5 ]. In addition, some reports have related external discoloration of the resin composite to large filler particles as they provide increased surface roughness [ 17 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse effects of CHX present in mouthwashes have been reported (dysgeusia and dental pigmentation being among the most common) depending on its dosage. This has led to the suggestion over the years of different CHX concentrations to balance beneficial and adverse effects in order to improve patient treatment [ 24 ]. The Food and Drug Administration (FDA) suggests the use of CHX as a mouthwash in 10 to 20 mL presentations with concentrations of 0.12% and 0.2% for approximately 30 s and for a period that can vary between 2 and 4 weeks [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic therapy (amoxicillin and clavulanic acid 1 g or clarithromycin 1 g in case of allergy, twice daily for 7 days after surgery) and analgesic treatment (non-steroidal anti-inflammatory drugs, as required) were prescribed for each patient. Mouth rinses with a solution of chlorhexidine-digluconate (0.20%) twice daily for 10 days were recommended [ 40 , 41 , 42 ]. One week after the surgery, the sutures were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Cetyl pyridium chloride has been used, investigated and proved that it is as efficient as chlorhexidine is in combination with the alcohol along with, this new formulation reduces the unpleasant side effects of mucosal irritation. [3][4][5][6][7][8][9] The most common side effect by the use of the chlorhexidine mouthwash is brownish discoloration of the teeth, brownish discoloration of restoration if present in the oral cavity, and discoloration of the tongue. Staining which has been done by the use of chlorhexidine mouth wash, can not be easily removed with the help of tooth brushing.…”
Section: As An Antiplaque Agentmentioning
confidence: 99%
“…Alternative to this, use of chlorhexidine chip, containing 2.5 mg of chlorhexidine which is present in cross linked matrix of gelatin is placed in to the periodontal pocket, results in inhibition of the bacteria up to 99 %. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Chlorhexidine also helps in the treatment of oral malodor. The use of chlorhexidine after any periodontal surgery, results in enhancing the wound healing.…”
Section: Use In Periodontal Therapymentioning
confidence: 99%